Prediction of nocturnal ventilation by pulmonary function testing in patients with amyotrophic lateral sclerosis - Tress, Friederike; Luecke, Eva; Stegemann-Koniszewski, Sabine; Lux, Anke; Singla, Abhinav; Schreiber, Jens (Pneumologie, 2024)
Background In amyotrophic lateral sclerosis (ALS) prognosis is poor due to progressive weakening of the respiratory muscles. Survival and quality of life can be improved by noninvasive ventilation (NIV), which is initially applied while sleeping. The indication for NIV is based on pulmonary function testing (PFT) and polysomnography (PSG) with capnography (tCO2). While it is desirable to predict nocturnal ventilation by waking PFT in ALS, the parameters suited for reliable predictions remain elusive. Methods We retrospectively analyzed parameters derived from PFT (spirometry, body plethysmography, diffusion capacity, respiratory muscle testing) and blood gas analysis, PSG and tCO2 in 42 patients with ALS (27 men, 15 women, age 69 ± 12.1 years) and performed Spearman’s correlation analysis of daytime waking parameters and nighttime sleep parameters. Results 28 patients (66.7%) showed restrictive impairment of ventilation and 15 patients (48.3%) showed insufficiency of the respiratory musculature. There was no obstructive impairment of ventilation. We did not observe any significant correlations between any single daytime PFT parameter with nocturnal pCO2. However, there were significant correlations between the ratios PIF/PEF, MEF50/MIF50, DLCO/VA as well as FEV1/FVC and nocturnal pCO2. Highly normal FEV1/FVC and Krogh-Factor (DLCOc/VA) indicated nocturnal hypercapnia. Furthermore, waking hypercapnia, concentrations of bicarbonate and base excess were each positively correlated with nocturnal hypercapnia. Conclusions Waking PFT is not a good predictor of nocturnal ventilation. Inspiratory parameters as well as the ratios FEV1/FVC and DLCO/VA performed best and should be included in the interpretation. Our analyses confirm the relevance of inspiratory muscle weakness in ALS. PSG and tCO2 remain the gold standard for the assessment of nocturnal ventilation.
Keywords: amyotrophic lateral sclerosis; polysomnography; noninvasive ventilation; pulmonary function testing; nocturnal ventilation